Preparation and Properties of Novel Semi-Aromatic Co-Polyamide 6T/6 - Han, Bing; Zhang, Chunxiang; Feng, Zhiming; Zhang, Shengchun; Gu, Xiaohua; Zhang, Kejie; Xu, Zhibin (Asian Journal of Chemistry, 2014)
Semi-aromatic co-polyamides 6T/6 was synthesized via solution polymerization using terephthalic acid, 6-diaminohexane and caprolactam as raw materials. The structure of the obtained samples was characterized by fourier transform infrared spectroscopy. The influence of solid-phase reaction on the melting point and melt index of copolymer and the effect of oligomer content and intrinsic viscosity on the mechanical properties were also discussed. The results show that the intrinsic viscosity can be adjusted by the solid-phase polymerization process, while the latter has no significant effect on the melting points. The intrinsic viscosity of the copolymer and the content of the monomer have a significant impact on the mechanical properties of materials.